Innovative percutaneous antegrade clearance of intrahepatic and extrahepatic biliary stones with the use of a hysterosalpingography catheter. Issue 4 (April 2015) - Patrone, Lorenzo; Parthipun, Aneeta; Diamantopoulos, Athanasios; Pinna, Francesco; Valdata, Alessandro; Ahmed, Irfan; Filauro, Marco; Sabharwal, Tarun; de Caro, Giovanni
Abstract : Objectives: We present a novel modified technique of percutaneous antegrade clearance of intrahepatic and common bile duct stones with the use of a hysterosalpingography balloon (HSG) catheter. Methods: Technical tips and techniques used, along with the clinical results obtained in six patients whom we treated over a 6-month period have been described. Results: The HSG balloon catheter is shown to demonstrate superior pushability, flexibility, and maneuverability in comparison with other previously described compliant balloons. Conclusions: The HSG balloon catheter is shown to be a really good device to remove intrahepatic and common bile duct stones percutaneously, allowing, where required, access to both the right and the left intrahepatic biliary systems from a single and smaller Fr hepatic bile duct access.